Role Of Deputy Channabasappa in The Development of Education in The Colonial Rule of Mumbai Karnataka - Kakasaheb Laxman Gasti (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This article examines the pivotal role of Deputy Channabasappa in advancing education and the Kannada language during the Colonial Rule in the Mumbai-Karnataka region (Belagavi and Dharwad). Born in 1833, Channabasappa overcame financial hurdles to gain an education, including engineering, at Pune. His dedication to his mother tongue led him to a remarkable career in the education department. As the first principal of the upgraded Teachers’ Training College in Belagavi (1864) and later as Deputy Education Inspector, he tirelessly promoted Kannada. He mandated the use of Kannada in teaching and communication, established schools, developed textbooks, and passed circulars to strengthen the language’s status, ensuring the region remained distinctly Kannada-speaking despite strong Marathi influence. His efforts laid a strong foundation for the language’s growth and eventual administrative recognition.